A taxonomic revision of the Neotropical poison frog genus Ranitomeya (Amphibia: Dendrobatidae) - Brown, Jason L.; Twomey, Evan; Amézquita, Adolfo; de Souza, Moisés Barbosa; Caldwell, Janalee P.; Lötters, Stefan; Von May, Rudolf; Melo-Sampaio, Paulo Roberto; Mejía-Vargas, Daniel; Perez-Peña, Pedro; Pepper, Mark; Poelman, Erik H.; et al. (Zootaxa, 2011)
The Neotropical poison frog genus Ranitomeya is revised, resulting in one new genus, one new species, five synonymies and one species classified as nomen dubium. We present an expanded molecular phylogeny that contains 235 terminals, 104 of which are new to this study. Notable additions to this phylogeny include seven of the 12 species in the minuta group, 15 Ranitomeya amazonica, 20 R. lamasi, two R. sirensis, 30 R. ventrimaculata and seven R. uakarii. Previous researchers have long recognized two distinct, reciprocally monophyletic species groups contained within Ranitomeya, sensu Grant et al. 2006: the ventrimaculata group, which is distributed throughout much of the Amazon, and the minuta group of the northern Andes and Central America. We restrict Ranitomeya to the former group and erect a new genus, Andinobates Twomey, Brown, Amézquita & Mejía-Vargas gen. nov., for members of the minuta group. Other major taxonomic results of the current revision include the following: (i) A new species, Ranitomeya toraro Brown, Caldwell, Twomey, Melo-Sampaio & Souza sp. nov., is described from western Brazil. This species has long been referred to as R. ventrimaculata but new morphological and phylogenetic data place it sister to R. defleri. (ii) Examination of the holotype of R. ventrimaculata revealed that this specimen is in fact a member of what is currently referred to as R. duellmani, therefore, Dendrobates duellmani Schulte 1999 is considered herein a junior synonym of D. ventrimaculatus Shreve 1935 (= R. ventrimaculata). (iii) For the frogs that were being called R. ventrimaculata prior to this revision, the oldest available and therefore applicable name is R. variabilis. Whereas previous definitions of R. variabilis were restricted to spotted highland frogs near Tarapoto, Peru, our data suggest that this color morph is conspecific with lowland striped counterparts. Therefore, the definition of R. variabilis is greatly expanded to include most frogs which were (prior to this revision) referred to as R. ventrimaculata. (iv) Phylogenetic and bioacoustic evidence support the retention of R. amazonica as a valid species related to R. variabilis as defined in this paper. Based on phylogenetic data, R. amazonica appears to be distributed throughout much of the lower Amazon, as far east as French Guiana and the Amazon Delta and as far west as Iquitos, Peru. (v) Behavioral and morphological data, as well as phylogenetic data which includes topotypic material of R. sirensis and numerous samples of R. lamasi, suggest that the names sirensis, lamasi and biolat are applicable to a single, widespread species that displays considerable morphological variation throughout its range. The oldest available name for this group is sirensis Aichinger; therefore, we expand the definition of R. sirensis. (vi) Ranitomeya ignea and R. intermedia, elevated to the species status in a previous revision, are placed as junior synonyms of R. reticulata and R. imitator, respectively. (vii) Ranitomeya rubrocephala is designated as nomen dubium. In addition to taxonomic changes, this revision includes the following: (i) Explicit definitions of species groups that are consistent with our proposed taxonomy. (ii) A comprehensive dichotomous key for identification of ‘small’ aposematic poison frogs of South and Central America. (iii) Detailed distribution maps of all Ranitomeya species, including unpublished localities for most species. In some cases, these records result in substantial range extensions (e.g., R. uakarii, R. fantastica). (iv) Tadpole descriptions for R. amazonica, R. flavovittata, R. imitator, R. toraro sp. nov., R. uakarii and R. variabilis; plus a summary of tadpole morphological data for Andinobates and Ranitomeya species. (v) A summary of call data on most members of Andinobates and Ranitomeya, including call data of several species that have not been published before. (vi) A discussion on the continued impacts of the pet trade on poison frogs (vii) A discussion on several cases of potential Müllerian mimicry within the genus Ranitomeya. We also give opinions regarding the current debate on recent taxonomic changes and the use of the name Ranitomeya.